"Kwentong Hiwalayan" a framing analysis of pro-divorce married Filipinas and the affordances for practice of Facebook-based divorce advocacy groups in the Philippines - De Castro, Karylle Gray; Solarte, Charmagne R.
This study examines how pro-divorce married Filipinas (PDMFs) use Facebook groups to share adverse marital narratives and mobilize collective resistance. Anchored in Benford and Snow’s (2000) collective action framing and Fayard and Weeks’ (2014) affordances for practice, it draws from textual analysis and interviews with administrators and moderators of two major advocacy groups: Pilipinas Marital Reform Network (PMRN) and Global Advocates for Divorce Rights PH (GADR-PH). Findings show that PDMFs used diagnostic frames to expose polyvictimization, betrayal, cultural guilt, and institutional neglect. Prognostic frames reimagine divorce as a necessary, life-affirming solution that defies religious and societal pressures. Motivational frames position divorce as an act of freedom, strength, and maternal love. Facebook’s affordances, like storytelling, anonymity, and moderation tools, enable strategic self-expression and emotional survival, but advocacy remains precarious. Internal group tensions and Meta’s unpredictable censorship threaten the continuity of their safe spaces.